FAKTOR-FAKTOR KECURANGAN AKUNTANSI DI PEMERINTAH DAERAH DAN PERAN ETIKA ISLAM DALAM PENCEGAHANNYA - Dani Kusumastuti (el-Jizya: Jurnal Ekonomi Islam, 2019)
Purpose - Corruption in local government is becoming increasingly prevalent. This has become an irony amid the vigorous development in the era of regional autonomy. To deal with this problem, this study is aimed to identify the factors of fraud in the local governments of Indonesia and to investigate whether the application of Islamic ethic can prevent accounting fraud. Design/methodology/approach – To achieve this goal, this study collects and compares the results of various quantitative empirical studies in various local governments throughout Indonesia that have been carried out in the past three years (2015-2017). The data will be synthesized and conclusions drawn in this study to answer research questions. The data is obtained in journals traced in several electronic media such as digital libraries, internet or library journal collections. The keywords used for search are: factors, accounting fraud, fraud, prevention and local government. Findings – The results provide evidences that indicate that accounting fraud in local goverments of Indonesia is significantly influenced by factors explained in Fraud theory. It is also proved from empirical studies that the implementation of Islamic ethic is useful to prevent fraud within local goverments in Indonesia. Research limitations/implications –The result of the paper contribute to the literature in understanding of how to prevent accounting fraud especially within the local governments in Indonesia by developing approaches based on Islamic ethics. Originality/value – Findings are useful for policy makers and local goverments to handle accounting fraud cases and enhance their accounting fraud prevention system by applying Islamic ethics.